URGENSI PERJANJIAN PENGIKATAN JUAL BELI TERHADAP TANAH YANG BELUM BERSERTIFIKAT DI INDONESIA - Ni Komang Pramudiasari; I Kadek Dony Hartawan; Ni Komang Irma Adi Sukmaningsih (Universitas Pendidikan Ganesha, 2026)
This study focuses on evaluating the legal framework of the Sale and Purchase Binding Agreement (PPJB) for uncertified land in Indonesia and formulating an ideal regulatory model to ensure legal protection and certainty for all parties involved. The primary driver of this research is the lack of specific regulations governing PPJB on uncertified land, which forces its practical implementation to rely merely on general contract law, overall agrarian provisions, and customary notarial practices. This circumstance creates a normative void that risks causing inconsistent procedures and legal disputes. Utilizing statutory and conceptual approaches, this normative legal research analyzes primary, secondary, and tertiary legal sources through qualitative examination. Findings reveal that current Indonesian laws do not comprehensively govern PPJB for uncertified land, leaving its enforceability dependent strictly on the freedom of contract principle under the Civil Code. Consequently, dedicated regulations are urgently required to define the legal standing of PPJB, land eligibility standards, mandatory contractual terms, notarial duty of care, protections for good-faith buyers, and dispute resolution channels. Such legislation is expected to establish legal certainty, procedural uniformity, and enhanced legal safeguards.